Highlighting the Effect of Interfacial Interaction on Tribological Properties of Supramolecular Gel Lubricants. Issue 3 (30th November 2015) - Huang, Guowei; Yu, Qiangliang; Cai, Meirong; Zhou, Feng; Liu, Weimin
Abstract : The effect of the frictional interfacial interaction of two types of gel lubricants on lubrication mechanisms is investigated. The structure of the two types of gelators, polyhydric gelator (PG) and thiol functionalized polyhydric gelator (FPG), is identical except for one of them having thiol groups. The tribological properties of these gels as lubricants are evaluated for the contacts of steel/steel, steel/aluminum, steel/copper, and steel/alumina ceramic. It is shown that these gels have better friction reduction and antiwear (AW) performance than blank 500SN. Under medium–high pressure, the gel at the interface is liquefied and a growing number of gelator molecules will adsorb onto the metal surface by polar hydroxyl and thiol headgroups. Hydroxylation treatment of sliding pairs can significantly enhance the interfacial absorption interaction and improve tribological properties. Interestingly, FPG gel lubricant exhibits better lubricating and AW properties compared with PG gel under the same test conditions. Quartz crystal microbalance (QCM) measurements suggest that FPG containing the thiol and hydroxyl dual polar groups has better adsorption ability on the contact surface than PG only with hydroxyl groups. FPG gel lubricants therefore form more robust protective films. Abstract : Gel lubricants are prepared by supramolecular assembly of nonionic surfactant gelators in mineral oils. As lubricants for various sliding friction pairs, these gels have better friction reduction and antiwear performance than blank 500SN. The excellent tribological performance of the gels is attributed to the formation of robust adsorption films with their thiol and hydroxyl polar groups on rubbing surfaces.